Study of work of PVC membranes for engineering waterproofing under increased seismic conditions - V. N. Shalimov; A. V. Tsybenko; I. N. Goglev; S. A. Loginova (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. At present, increased requirements are imposed on waterproofing materials used in seismic hazard zones. The aim of the study is to assess the possibility of using LOGICBASE™ polymer membranes in regions of increased seismic activity in the Russian Federation.Method. The mechanism of operation of polymeric membranes in foundation structures under conditions of constant displacement and friction is considered. Experiments were carried out to determine the coefficient of friction according to the method of state standards on a tensile testing machine MIRK-1000K. Samples of a round shape made of polymeric membranes were studied on a special multiaxial stretching device in accordance with the requirements of state standards.Result. Multiaxial tensile testing of LOGICBASE™ V-SL polymeric membranes revealed that the maximum tensile strength of the samples was 6948.22 kPa (~ 6.95 MPa), and the elongation of the samples at break was 113.89%. The coefficient of friction in the system "polymer waterproofing material - concrete structure" was determined under conditions of increased seismic activity according to the MSK-64 scale.Conclusion. According to the studies, it was concluded that PVC membranes for engineering waterproofing can be used in construction areas with seismicity up to 9 points inclusive on the MSK-64 scale.